Imagens da violência e a violência das imagens. as narrativas imagéticas de violências nos livros didáticos de história do ensino médio. - Morais, Ana Meyre de (Universidade Federal Rural do Semi-Árido, 2019)
In different periods of history, violence has been translated into practices, intimidation, silences, imprisonment undertaken by various peoples, sometimes subtly, sometimes explicitly. Currently, many forms of violence gain sensationalist highlights in different media spaces, sometimes generating the trivialization of what should be reflected, analyzed and questioned also in classrooms. It is observed that the images of violence are spread in different places and means. History textbooks are not the exception, even though violence is thought of only as a consequence of facts and acts of the characters, heroes, enemies, foreigners, and others. The textbooks do not only serve to disseminate, but make the reflection is a consequence of the contents taught. The school environment becomes not only a place of knowledge production, but a space where one can approach different delicate subjects. The purpose of this research was therefore to analyze the images of violent nature present in high school history textbooks, to observe how this theme can help students become critical, reflective and active during their education. To this end, the methodology featured a cataloging of images that can be translated as violent, present in the Past and Present History Collection of High School. Secondly, the analysis of the images were a historiographical documentary reference that greatly influences the quality of teaching. About the images, we tried to draw a documentary criticism in the light of the Histories of the Images. Therefore, theoretically, this research was anchored in: Santaella (2012), Bittencourt (2004, 2009), Muller (1995), Arendt (1970), Pinsky (1994), Cassiano (2013), Odalia (2012), Bardin ( 2011), Gil (2008). The result showed that violent images offer ways to enhance not only the teaching of history, but also the way students read and perceive iconographic records.
Keywords: Imagens da violência; Livro didático de História; Ensino de História; Images of violence; History textbook; History teaching; MULTIDISCIPLINAR::ENSINO